Prevalence of Post-Spinal Anesthesia Shivering and Associated Factors in Patients Undergoing Cesarean Section with Spinal Anesthesia in Lady Reading Hospital Peshawar, Pakistan - M Haseeb Moin Ud din Baloch; Amjad, Afnan; Sayed Shah Hassanain; Muhammad Aftab Ahmad; Ayesha Tufail; Muhammad Izaz (Journal of Postgraduate Medical Institute, 2024)
Objective: To determine the prevalence of Post-spinal anesthesia shivering and associated factors in patients undergoing Cesarean section Surgery in Lady Reading Hospital Peshawar. Methodology: This observational study was conducted in Lady Reading Hospital Peshawar. One hundred seventy-three patients were included in the study undergoing Spinal Anesthesia for elective or emergency caesarian section from June 2023 to September 2023. ASA class II (American Society of Anesthesiologists) and class III patients were recruited into the study, and non-consenting were excluded. A standard dose of 0.5% bupivacaine was administered as spinal anesthesia and standard monitoring recording was conducted every 5 minutes during the surgery. Shivering was monitored till the discharge of the patient to the ward. Results: Out of 173 patients included in the study, only 18 surgeries were elective, and the rest, 155, were emergency cesarean section surgeries. Among emergency surgeries, the highest number of indications was Poor progression of labor, 29.6%. Post-spinal anesthesia shivering was recorded in 146 patients, 15.6%. Most of the post-spinal anesthesia was also associated with Hypothermia (92.5%) and hypotension (96.2%). Conclusion: Post-spinal shivering was observed in 15.6% of the patients, with hypothermia and hypotension as associated factors.